2019
DOI: 10.1002/hbm.24695
|View full text |Cite
|
Sign up to set email alerts
|

Network spread determines severity of degeneration and disconnection in Huntington's disease

Abstract: Trans‐neuronal propagation of mutant huntingtin protein contributes to the organised spread of cortico‐striatal degeneration and disconnection in Huntington's disease (HD). We investigated whether the network diffusion model, which models transneuronal spread as diffusion of pathological proteins via the brain connectome, can determine the severity of neural degeneration and disconnection in HD. We used structural magnetic resonance imaging (MRI) and high‐angular resolution diffusion weighted imaging (DWI) dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 46 publications
4
49
0
Order By: Relevance
“…Using longitudinal data from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) database, Torok and colleagues (2018) showed that NDM and an inference optimization algorithm can successfully infer the regions of disease initiation (referred as seed regions) from which Alzheimer’s disease or Mild Cognitive Impairment tau pathology most likely originated. Our recent study demonstrated that the spread of mutant huntingtin protein, via the human brain connectome, accurately predicted the cortico‐striatal spatial pattern of degeneration in patients with Huntington’s disease. The NDM framework was also recently used for capturing the spatiotemporal progression of Parkinson’s disease .…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Using longitudinal data from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) database, Torok and colleagues (2018) showed that NDM and an inference optimization algorithm can successfully infer the regions of disease initiation (referred as seed regions) from which Alzheimer’s disease or Mild Cognitive Impairment tau pathology most likely originated. Our recent study demonstrated that the spread of mutant huntingtin protein, via the human brain connectome, accurately predicted the cortico‐striatal spatial pattern of degeneration in patients with Huntington’s disease. The NDM framework was also recently used for capturing the spatiotemporal progression of Parkinson’s disease .…”
Section: Introductionmentioning
confidence: 93%
“…The present study employed a model of spread of pathology via brain networks based on the network diffusion model (NDM) . A growing number of studies have utilized NDM as a means to model the progression of neurodegenerative pathology on brain networks .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Post-mortem histopathological analyses (Braak and Braak, 1991; Braak et al, 2003; Brettschneider et al, 2013) and in vivo imaging studies (Deng et al, 2004; Poudel et al, 2019) indicate that proteopathic lesions associated with neurodegeneration appear in highly-reproducible and disease-specific spatiotemporal patterns through the brain. Interestingly, these patterns largely follow neuroanatomical tracts (Ahmed et al, 2014; Mezias et al, 2017), suggesting a central role for synaptic connectivity in pathological aggregate spreading.…”
Section: Introductionmentioning
confidence: 99%